Recent Developments in Visible-Light-Catalyzed Multicomponent Trifluoromethylation of Unsaturated Carbon–Carbon Bonds - Oh, Eun Hye; Kim, Hyun Jin; Han, Soo Bong (Synthesis, 2018)
Trifluoromethylation has emerged as an important tool for modulating the molecular chemical and physical properties in material, polymer, and medicinal chemistry. In particular, photocatalyzed trifluoromethylation in the presence of visible-light irradiation has potentially different activity under mild conditions compared with traditional methods. This review summarizes the recent advances in trifluoromethylation with multiple bond system such as alkynes and alkenes.1 Introduction2 Trifluoromethylating Reagents3 Multicomponent Reactions of Alkynes4 Multicomponent Reactions of Alkenes5 Conclusion
Keywords: trifluoromethyl; radical; alkene; alkyne; photocatalyst; visible light